منهج النووي في التعامل مع "مختلف الحديث" وأثره في تنمية الملكة الفقهية الاستنباطية لدى طلاب الجامعات الإسلامية: دراسة تحليليّة تأصيليّة: Al-Nawawi’s Methodology in Addressing 'Mukhtalaf Al-Hadith' and Its Impact on Developing Deductive Jurisprudential Acumen Among Islamic University Students: A Foundational Analytical Study - Aswanto Muhammad Takwi Hede; Jamaluddin Jamaluddin (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
This study aims to examine and articulate the hadith-based and jurisprudential (usuli) methodology of Imam Sharaf al-Din al-Nawawi in addressing the issue of "Mukhtalaf al-Hadith" (traditions that appear to be contradictory), and to investigate the impact of this approach on developing the jurisprudential (fiqhi) acumen and independent reasoning (ijtihad) of students in Sharia faculties across Islamic universities. The research adopts an inductive-analytical approach by surveying and deconstructing the jurisprudential and hadith-based applications and pathways pursued by Imam al-Nawawi in his prominent work, "Al-Minhaj fi Sharh Sahih Muslim bin al-Hajjaj," while linking them to modern pedagogical and educational principles. The study reached several key findings, most notably: Imam al-Nawawi’s approach is characterized by a precise integration of hadith criticism and jurisprudential deduction (istinbat) to resolve apparent textual contradictions. This is achieved through a structured procedural sequence that begins with synthesis (jam‘), followed by abrogation (naskh), and then weighing/preference (tarjih), while interpreting subordinate texts in a manner consistent with the abrogating and preferred ones. Furthermore, this research contributes to developing an integrated applied model that links the jurisprudential rules for "Mukhtalaf al-Hadith" according to Imam al-Nawawi with the mechanisms for building jurisprudential and deductive acumen among university students; thus bridging the gap between theoretical principles and applied tradition in contemporary academic curricula. The research also provides a clear procedural roadmap that helps transform traditional critical thinking skills into measurable and teachable competencies within the university environment. The study recommends the necessity of transitioning hadith curricula in universities from narrative-based, rote memorization toward practical labs for training the "contemporary mujtahid." It also advocates for shifting the study of classical commentaries from a passive lecturing style to an active case-study approach based on jurisprudential principles.